LUIS DE VALDIVIA AND ALONSO MEJIA: A PERSONAL RELATION IN THE ORIGINS OF VALDIVIA’S THOUGHT (1602-1604) - Díaz Blanco, José Manuel; Gaune, Rafael (Revista de Historia Social y de las Mentalidades, 2015)
This study investigates the influence that Father  Alonso Mejia could have had on the crucial  intellectual change experienced by Father Luis  de Valdivia in Lima between 1602 and 1604.  To resolve the issue, it uses a comparative  methodology, which intersects the biographies of  both Jesuits and their most relevant writings in  that regard: a memorial written by Mejía in 1603  and a report from Valdivia composed in 1604.  The information that such analysis provides  establishes the intellectual similarities between  the two Fathers, as well as the biographical  coincidences that brought them together,  supporting the conclusion that, indeed, Mejia  must have had a major influence in defining the  political thought of Valdivia
Keywords: Luis de Valdivia,; Alonso Mejía; Personal service; Mapuche revolt